Non-native English Speaking Teacher (NNEST) and their Delivery (Journal of NELTA, 2018)
This article attempts to display the characteristics of the non-native English speaking teachers (NNESTs) and focuses on the need for the transition of their potentialities in various circumstances of their career. It also describes some of the issues related to their shared difficulties and insecurities, and uncovers the strategies that help them to build up their mind and vision. The non-native speakers of English are definitely in a strong position as teachers in that they can use their experiences to bring quality to teaching and become more effective speakers of English. In addition, the article highlights the non-native speakers of English scenario with the intention to promote further in-depth research on this unexplored area of “non-nativesness.” The article also makes a brief description of the problems the Nepali NNESTs face in their classroom delivery processes and discusses ways to overcome them.Journal of NELTA ,  Vol. 22, No. 1-2, 2017 December, Page: 117-126